Strengthening co-operation with countries of origin (Paris, 2016)
"This paper is part of the joint project between the Directorate General for Migration and Home Affairs of the European Commission and the OECD’s Directorate for Employment, Labour and Social Affairs on "Review of Labour Migration Policy in Europe". This document has been produced with the financial assistance of the European Union. The views expressed herein can in no way be taken to reflect the official opinion of the European Union. Grant: HOME/2013/EIFX/CA/002 / 30-CE-0615920/00-38 (DI130895) A previous version of this paper was presented and discussed at the OECD Working Party on Migration in June 2015.The paper presents the main instruments for co-operation with third countries in the area of labour immigration – policy instruments constituted by the mobility partnerships, financial instruments, as well as legal instruments. For each of them, the study examines the reference sources underpinning the activity, the manner in which labour immigration is organised, and the ways of promoting ethical recruitment. The paper then draws up a frame of reference on these instruments, followed by specific references to the labour immigration policies of certain Member States, and certain third countries, serving to illustrate the arguments."